PELATIHAN DAN PENDAMPINGAN GURU PAUD DALAM INOVASI MODEL PEMBELAJARAN BERBASIS KELOMPOK DENGAN PENDEKATAN STUDENT CENTERED DI KB/RA THARIQUN NAJAH SELETRENG - Farhatin Masruroh; Khulusinniyah Khulusinniyah (LP2M Universitas Ibrahimy, 2020)
KB / RA teacher training and mentoring activities in the innovation of group-based learning models with the student-centered approach is an attempt to change learning from conventional classical models and teacher-centered to group-based learning that is centered on the activities of students. This activity goes through three stages, namely planning, implementation, and evaluation. At the planning stage, the problem identification process is carried out, making work plans (work plans), and classifying teaching practices (peer teaching). At the implementation stage, it consists of two stages; 1) group learning model training with a student-centered approach which includes group model class management techniques, learning media design, and evaluation techniques.